The role of Libyan women in achieving development and development of society: Women in the city of Sebha as a model (Journal of Human Sciences, 2024)
This study aims to explain the concept and dimensions of sustainable development, identify the role played by Libyan women in the city of Sebha in social and economic activities, and finally highlight the difficulties and challenges that hinder Libyan women in the city of Sebha in sustainable development and community development. Women are considered effective elements and contributors to the development of society. Therefore, its development mission has become the advancement of society for the better, and on this basis the study starts from a basic hypothesis which is to verify the extent of women’s role in achieving sustainable development, through the realistic experiences that women in the city of Sabha have undergone in all developmental, social and economic fields. This study follows an approach Inductively using descriptive analysis through the qualitative approach by conducting personal interviews with female leaders in the city of Sabha as a tool for collecting data.One of the most prominent results of the study is that Libyan women, specifically women in the city of Sebha, made a significant contribution to achieving sustainable development in social activity in terms of helping poor families, helping young people in some areas, and establishing many projects with women of limited income, and also contributed to achieving useful and fruitful social communication and encouraging... Others to set up projects. As for their economic activity, from the point of view of the respondents, it was found that there is no support from the state. Most families depend on their income to participate in their economic activities from associations with individual or community projects, such as: holding exhibitions, courses, sewing activities, and traditional food. The difficulties and challenges that hinder Libyan women in the city of Sabha in sustainable development and community development were represented by the woman herself or in her social environment. And also customs and traditions, the difficulty of women in the city of Sabha in moving from one place to another, and society’s view of women in the city of Sabha through her playing a secondary role in this matter.It is hoped that this study has contributed to shedding light on reconciling the role of Libyan women with sustainable development and community development as two important variables in the current era in all fields.